2007
DOI: 10.1007/s11998-007-9041-0
|View full text |Cite
|
Sign up to set email alerts
|

A study of new manganese complexes as potential driers for alkyd paints

Abstract: In the search for new autoxidation catalysts, the oxidative crosslinking of ethyl linoleate (EL) has been monitored using time-resolved FT-IR (Fourier transform IR spectroscopy), size-exclusion chromatography and GC/MS (gas chromotography/mass spectroscopy). These methods seem to be quite sensitive to changes in the structure of the catalyst. It has been found that the compound [Mn(acac) 3 ] (Hacac = 2,4-pentanedione) is an efficient catalyst for the oxidation and the oligomerization of EL, which is proposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 30 publications
0
38
0
Order By: Relevance
“…Other studies, however, found that linseed oil films reached a maximum mass within several days of curing and then began losing mass [14,20]. This mass loss is the result of the formation of volatile products from oxidation reactions [35,36].…”
Section: Long-term Curingmentioning
confidence: 95%
“…Other studies, however, found that linseed oil films reached a maximum mass within several days of curing and then began losing mass [14,20]. This mass loss is the result of the formation of volatile products from oxidation reactions [35,36].…”
Section: Long-term Curingmentioning
confidence: 95%
“…10,22,23 FT-IR spectra of HS alkyd coatings were recorded after different times. Relative reaction rates have been calculated with linear regression of the ln (A t /A 0 *100) versus time after the induction period.…”
Section: Time Resolved Ft-ir Experiment: Evaluation Of Chemical Cumentioning
confidence: 99%
“…The quest is stimulated by European REACH (Registration, Evaluation, Authorization, and Restriction of Chemicals) legislation since they have been classified as “CMR2‐Reprotoxic” by the Cobalt REACH Consortium. Recently, several manganese, iron, and vanadium‐based driers, suitable for alkyd binders, have been described in literature and some of them are already commercially available. Nevertheless, most of the alternatives still suffer several disadvantages (i.e., low solubility in formulation, intense coloration).…”
Section: Introductionmentioning
confidence: 99%